Meeting the Dalai Lama and perceptions of democracy in China: a quasi-natural experiment. Issue 4 (19th May 2018) - Gruffydd-Jones, Jamie J.
ABSTRACT: How does the international human rights community affect the likelihood of democratization? Scholarship on Chinese citizens' preferences about their political system has not explored the importance of the external environment, perhaps surprising given the extensive foreign pressure on China's authoritarian system over the last 30 years. I use a quasi-natural experiment around the meeting between President Obama and the Dalai Lama in 2011 to examine the impact of foreign pressure on citizens' perceptions of democracy in China in real time. I show that the meeting significantly increased the Chinese public's belief that their country is democratic, with those of above average patriotism over 11 percentage points more likely to believe China is democratic in the five days following the meeting than before. The findings suggest that some kinds of external pressure may help to increase satisfaction with authoritarian rule, ultimately boosting autocrats' ability to hold on to power.